Republic of Moldova : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion; Staff Report; Staff Supplement; and Press Release. (IMF Staff Country Reports; Country Report, 2008)
This paper examines the Republic of Moldova's Fourth Review under the Poverty Reduction and Growth Facility and request for Waiver of Nonobservance of Performance Criterion. Investors have been attracted by Moldova's low costs, and export prospects have improved with the resumption of wine exports to Russia and a new trade agreement with the European Union. Inflation is the main concern. While rising inflation partly reflects regional trends in food and energy prices, strong demand has been adding to inflation pressures.